Gate‐Tunable Hole and Electron Carrier Transport in Atomically Thin Dual‐Channel WSe2/MoS2 Heterostructure for Ambipolar Field‐Effect Transistors. Issue 43 (13th September 2016) - Lee, Inyeal; Rathi, Servin; Lim, Dongsuk; Li, Lijun; Park, Jinwoo; Lee, Yoontae; Yi, Kyung Soo; Dhakal, Krishna P.; Kim, Jeongyong; Lee, Changgu; Lee, Gwan‐Hyoung; Kim, Young Duck; et al.
Abstract : An ambipolar dual‐channel field‐effect transistor (FET) with a WSe2 /MoS2 heterostructure formed by separately controlled individual channel layers is demonstrated. The FET shows a switchable ambipolar behavior with independent carrier transport of electrons and holes in the individual layers of MoS2 and WSe2, respectively. Moreover, the photoresponse is studied at the heterointerface of the WSe2 /MoS2 dual‐channel FET.